Dietary caloric input and tumor growth accelerate senescence and modulate liver and adipose tissue crosstalk - José Xavier do Nascimento Júnior; Júlia da Conceição Gomes; Ricardo Imbroisi Filho; Helber de Maia Valença; Jéssica Ristow Branco; Amanda Bandeira Araújo; Amanda de Oliveira Esteves Moreira; Letícia Diniz Crepaldi; Larissa Pereira Paixão; Alan C. Ochioni; Thainá M. Demaria; João Gabriel Bernardo Leandro; et al. (Communications Biology)
Abstract Metabolic alterations are related to tumorigenesis and other age-related diseases that are accelerated by “Westernized” diets. In fact, hypercaloric nutrition is associated with an increased incidence of cancers and faster aging. Conversely, lifespan-extending strategies, such as caloric restriction, impose beneficial effects on both processes. Here, we investigated the metabolic consequences of hypercaloric-induced aging on tumor growth in female mice. Our findings indicate that a high-fat high-sucrose diet increases tumor growth mainly due to the boosted oxidation of glucose and fatty acids. Consequently, through an increased expression of lactate, IGFBP3, and PTHLH, tumors modulate liver and white adipose tissue metabolism. In the liver, the induced tumor increases fibrosis and accelerates the senescence process, despite the lower systemic pro-inflammatory state. Importantly, the induced tumor induces the wasting and browning of white adipose tissue, thereby reversing diet-induced insulin resistance. Finally, we suggest that tumor growth alters liver-adipose tissue crosstalk that upregulates Fgf21, induces senescence, and negatively modulates lipids and carbohydrates metabolism even in caloric-restricted-fed mice.